2011
DOI: 10.1002/cjoc.201190073
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Electronic Property of Passive Film on Nickel in Bicarbonate/Carbonate Buffer Solution

Abstract: The electronic properties of passive film formed on nickel in bicarbonate/carbonate buffer solution were studied by electrochemical impedance spectra (EIS) and Mott-Schottky plot. The film composition was analyzed by X-ray photoelectron spectroscopy (XPS). The results showed that passive film exhibited p-type semi-conductive character, and the acceptor density (N A ) decreased with increasing potential, prolonging time, decreasing temperature, increasing pH value and decreasing chloride/sulfur ions concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…One group has suggested that the low density of point defect causes high corrosion resistance. Extensive experimental results apparently agree with this opinion [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Other researchers have reported a high corrosion rate or a low corrosion resistance for the metals or alloys with passive films with low point defect density [38][39][40][41][42], corresponding to the results drawn from this work.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…One group has suggested that the low density of point defect causes high corrosion resistance. Extensive experimental results apparently agree with this opinion [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Other researchers have reported a high corrosion rate or a low corrosion resistance for the metals or alloys with passive films with low point defect density [38][39][40][41][42], corresponding to the results drawn from this work.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, the origin of such discordance is not yet known. Many of the reports included a proposition that the concentration of point defect would affect the stability of the passive film and hence the corrosion resistance but did not provide a mechanism supported theoretically [18,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…The two time constants feature is often considered as the response from an inhomogeneous passive film, which consists of a compact inner layer and a porous outer layer. It has been demonstrated that the passive films on nickel-base alloys can be more accurately described as a double layer structure composed of an n-type outer region containing Ni/ Fe oxide and hydroxide and a p-type inner region containing Cr oxide [44,61,62]. The low frequency time constant has been related to the inner barrier layer, and the time constant at high frequency range has been associated to the porous outer layer.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 97%
“…R 1 and Q 1 correspond to the resistance and capacitance of the porous layer which is responsible for the dissolution/precipitation processes through the passive film. R 2 and Q 2 represent the resistance and capacitance of the barrier layer that is responsible for the good resistance of the alloy [44,[61][62][63][64]. Macdonald and his co-workers [65][66][67] have proposed the point-defect model, involving the growth and destruction of the passive films.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Three different models, including adsorption leading to local passive film dissolution, penetration of anions in the passive film leading to weakening of the oxide bonds, and passive film break down at defects, such as cracks and dislocations, are frequently quoted to explain the effect of chloride ions on passive films and the influence of pitting corrosion (Li et al 2011;. The formation and dissolution of passive films, pitting corrosion of iron, and corrosive cracking of reinforced concrete in Na 2 SO 4 environment have also been reported (Gui and Devine 1994;Jin et al 2015).…”
Section: Introductionmentioning
confidence: 99%